The relationship between emotional intelligence and parental involvement towards academic achievement among student from Mengubah Destini Anak Bangsa program / Nurul Ain Mustakim …[et al.] - Mustakim, Nurul Ain; Hj Md Yusof, Dr. Rozman; Sauid, Muna Kameelah; Kamaruddin, Nurul Azwa (2012)
The purpose of this research is to highlight the impact of emotional intelligence and parental involvement on academic achievement and success in life among Mengubah Destini Anak Bangsa (MDAB) programmed students in a higher learning institution. Intelligence was found to be a major contributor to the success of a student. However, in this era emotional intelligence is vital in producing a good quality of graduate students. Emotional intelligence is proven to be the main predictor variable in the success of students performance and life. In addition, family plays a crucial role in the academic performance of students as parental involvement in education is encouraged to provide the spirit and revitalization of their children. This research makes a contribution to the debate about academic achievement and success in life among MDAB students in a higher learning institution and suggests that emotional intelligence should be taught in a university because it can be learned.